SUN-748 Functional Characterization of Estrogen-Regulated LncRNA16 in ER+ Breast Cancer - Yang, Barbara (J Endocr Soc, 2020)
Long noncoding RNAs (lncRNAs) have been demonstrated to be involved in diverse cellular processes as important regulators, such as in cancer. However, their roles in breast cancer biology are greatly unknown so far. In our study, integrated analysis of subcellular fractionation RNA-seq with gene expression profile from human reproductive tissues yielded a comprehensive catalog of estrogen-regulated reproductive tissue-specific lncRNAs. We selected long intergenic noncoding RNA 16 (LINC16) for further study as it was the top upregulated lncRNA by estrogen and associates with clinical outcome. Analysis of RNA-seq data from different human tissues, we found that LINC16 is highly expressed in testis and followed by other reproductive organs, cervix and uterus. Interestingly, interrogation of expression data from human cancer tissues showed LINC16 is highly expressed in breast cancer compared to other cancers. We have determined the 5’ and 3’ ends of LINC16 and its exon/intron structure, and cloned LINC16 to study its function in molecular and cell-based assays. Our preliminary results suggest that LINC16 plays a critical role in ERα-dependent pathways.